PELAKSANAAN SUPREMASI HUKUM DALAM RANGKA MENJUNJUNG TINGGI PENEGAKAN HUKUM YANG BERKEADILAN DAN BERTANGGUNG JAWAB PADA LEMBAGA PERADILAN - Amiruddin Amiruddin (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The 1945 Constitution of the Republic of Indonesia confirms that Indonesia is a state law. One of the important principles as a rule of law is further elaborated in the provisions of Law No.4 of 2004 concerning judicial power, namely the guarantee of the implementation of independent judicial power, free from the influence of other powers to administer to uphold law and justice. Law enforcement and justice are the main functions of the administration of justice to realize the implementation of the main tasks of judicial power in the context of implementing statutory regulations as mandated by the law concerning judicial power. For the administration of judicial power to run properly and optimally, the administration of judicial power that is independent, free from the influence of other powers is an absolute requirement in the context of law enforcement and justice today. Because only with the implementation of independent judicial power, free from the influence of other powers, the new law and justice can be enforced. It would be better if in the implementation of judicial power where law enforcement does not have independence, freedom, and conditions with intervention, then law and justice can't be enforced and realized, following the expectations of society. For this reason, the active role of all parties is needed to support the administration of independent judicial power, free from the influence of other powers for the sake of upholding law and justice. Because in essence, with the existence of independence and freedom in the world of law enforcement, it can open wide space and provide strengthening positions for judges in making decisions so that the image and authority of the court can be upheld. The implication is that the court can enforce the law on every case that is examined/tried, or in other words, the court can carry out its obligations by giving justice seekers the rights of the case submitted. In the implementation of the professionalism of judges in upholding the law in court, judges are obliged to provide equal rights and treatment to justice seekers as part of fulfilling the basic principles of independent judicial power. In addition to the guarantee of an honest trial process (open to the public) and rejecting/determining legal issues submitted in the form of freedom that is owned by judges to determine how the law is related to a problem.Keywords: Legal Supremation. Responsible Law